The Influence of Leadership, Competency, Motivation and Work Culture on Performance in the Regional Office of the Ministry of Religion, DKI Jakarta Province - Suwanto Suwanto (CV. Syntax Corporation Indonesia, 2023)
The background of this research is that the performance at the Regional Office of the Ministry of Religion of DKI Jakarta Province has not been optimal due to the lack of leadership roles, low competence, motivation and work culture. This research focuses on the variables of leadership, competence, motivation, work culture and performance. This study aims to analyze the influence of Leadership, Competence, Motivation, Work Culture on Performance either partially or together. The sampling technique in this study was proportionate stratified random sampling with a sample of 100 respondents. This research method is a quantitative approach method with multiple linear and regression analysis. Data collection techniques using documentation techniques, questionnaires, Focus Group Discussion (FGD), observation and literature study. The data collection tool in this study was a questionnaire based on a Likert scale. The data techniques in this research are validity test, reliability test, F test and t test, simple and multiple linear regression. The results of this study can be used as input for improving the performance of the Regional Office of the Ministry of Religion of DKI Jakarta Province through leadership, motivation and work culture efforts.